Method for preparing high-compaction lithium iron phosphate material from hydroxyl iron phosphate and application of high-compaction lithium iron phosphate material
Through the ratio of iron hydroxy phosphate to lithium phosphate and the addition of carbon source, high-compressed lithium iron phosphate material was prepared, which solved the problem of low compaction density of lithium iron phosphate material, and achieved efficient preparation of materials and improved battery energy density.
Patent Information
- Application Number
- CN202411902857.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-28
AI Technical Summary
The compaction density of existing lithium iron phosphate positive electrode materials is low, resulting in limited energy density of lithium-ion batteries. The preparation method is complex and costly, making it difficult to meet the needs of large-scale industrial production.
Through the ratio of iron hydroxy phosphate to lithium phosphate, carbon source and additives are added, and slurries of different particle sizes are prepared through sand milling, spray drying, sintering, and crushing. After mixing, spray drying, sintering, and crushing, and finally, high-pressure lithium iron phosphate material is obtained by adding carbon refractory.
It improves the compaction density and conductivity of lithium iron phosphate materials, simplifies the process flow, reduces production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119528106A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods for preparing positive electrode materials for lithium-ion batteries, and in particular to a method for preparing high-density lithium iron phosphate materials using hydroxyferric phosphate and application thereof. Background Art
[0002] Lithium iron phosphate cathode material is the fastest growing lithium battery cathode material in China. Its raw materials are widely available and inexpensive. It is widely used in the domestic battery industry in the fields of automobiles, power tools, energy storage equipment, emergency power supply equipment and mobile power supplies. Among them, new energy electric vehicles are the main application field, and the share of lithium iron phosphate accounts for more than 45% of the total lithium iron phosphate. However, the low energy density of lithium iron phosphate has always limited its further development. Although carbon coating can improve the conductivity of lithium iron phosphate, it will reduce the compaction density and energy density of lithium iron phosphate materials. Therefore, improving the compaction density of lithium iron phosphate materials and thus improving the energy density of lithium-ion batteries has become a research hotspot in recent years.
[0003] For example, the patent application with publication number CN103618083B obtains high-density lithium iron phosphate by three-fold tableting, but this method requires multiple tableting, crushing and sintering, the process is complicated, and the industrial production cost is high. The patent application with publication number CN106744780A prepares high-density lithium iron phosphate by using an iron source with high compaction density, but the overall yield of this method is low, which affects production capacity and is costly.
[0004] Although the above patent applications have improved the compaction density of lithium iron phosphate materials to a certain extent, there are still problems such as complex preparation methods, high production equipment requirements, and low production efficiency, which do not meet the current market needs for reducing the cost of lithium iron phosphate. Summary of the invention
[0005] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method and application of preparing high-density lithium iron phosphate material with hydroxy iron phosphate. The method uses hydroxy iron phosphate and lithium phosphate as raw materials to prepare two groups of slurries with different particle sizes, and then mixes the two groups of slurries in different proportions, dries, and pre-sinters them to obtain lithium iron phosphate, and then adds carbon and sinters them to finally obtain high-density lithium iron phosphate material. In addition, the method has high production efficiency and low production cost, and is suitable for application in large-scale industrial production.
[0006] To this end, the embodiment of the present invention provides a method for preparing a high-density lithium iron phosphate material by using hydroxy ferric phosphate, the method comprising: step S1: mixing hydroxy ferric phosphate with lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, sand milling, spray drying, sintering at a certain temperature, and crushing to obtain particles A; step S2: mixing hydroxy ferric phosphate with lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, ball milling, sand milling, spray drying, and sintering at a certain temperature to obtain particles B; step S 3: Add a carbon source, a dopant and a dispersant to the particles A, and then perform ball milling to obtain slurry C; Step S4: Add a carbon source, a dopant and a dispersant to the particles B, and then perform ball milling and sand milling to obtain slurry D; Step S5: Evenly mix slurry C and slurry D in a certain proportion to obtain mixed slurry E, and then spray dry, sinter, and crush to obtain a lithium iron phosphate precursor; Step S6: Add a certain amount of carbon source to the lithium iron phosphate precursor and mix evenly, and after sintering and crushing, a high-density lithium iron phosphate material can be obtained.
[0007] In some embodiments, in the step S1, the amount of the hydroxyferric phosphate and the lithium phosphate added is according to the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of the carbon source added is based on the carbon content in the particle A being between 0.01% and 0.20%; and the sanding particle size is controlled between 0.50 and 0.90 μm.
[0008] In some embodiments, in step S1, during spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blowing frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 700-800°C, and the sintering time is 5-15h; the particle size of the particles A is between 3.0-10.0μm.
[0009] In some embodiments, in step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the additive is one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300-3000ppm.
[0010] In some embodiments, in step S2, the amount of hydroxyferric phosphate and the lithium phosphate added is based on the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; and the sanding particle size is controlled between 0.40 and 0.80 μm.
[0011] In some embodiments, in step S2, during spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blowing frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 450-650°C, and the sintering time is 5-15h; the particle size of the particles B is between 2.0-5.0μm.
[0012] In some embodiments, in step S3, the amount of carbon source added is based on the carbon content in the slurry C being between 1.1% and 1.6%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant is one or more of titanium dioxide and ammonium metavanadate; and the particle size of the slurry C after ball milling is between 0.80 and 1.50 μm.
[0013] In some embodiments, in step S4, the amount of carbon source added is based on the carbon content in the slurry D being between 1.1% and 1.6%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant is one or more of titanium dioxide and ammonium metavanadate; and the particle size of the slurry D after sand grinding is between 0.20 and 0.50 μm.
[0014] In some embodiments, in the step S5, the slurry C and the slurry D are added in a mass ratio of slurry C: slurry D = 3:2. In spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, and the blowing frequency is 80Hz. During the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h. During the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the grading frequency is 80-200Hz. The particle size of the lithium iron phosphate precursor finally obtained satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
[0015] In some embodiments, in step S6, the mass of the carbon source added accounts for 0.25wt%-2.0wt% of the mass of the hydroxyferric phosphate precursor; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; during the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h; during the crushing process, the gas pressure is controlled between 0.2-0.4Mpa, and the grading frequency is 80-200Hz. The particle size of the high-density lithium iron phosphate material finally obtained satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
[0016] The method for preparing high-density lithium iron phosphate material from hydroxy iron phosphate provided in an embodiment of the present invention comprises mixing hydroxy iron phosphate, lithium phosphate, carbon source and additives twice, sintering, crushing, ball milling and sand milling at different temperatures to obtain two slurries with different particle sizes, and then mixing the two slurries in a certain proportion, spray drying, sintering and crushing to obtain a lithium iron phosphate precursor, and then adding carbon to the lithium iron phosphate precursor and sintering to prepare a high-density lithium iron phosphate material. The method of the present invention first prepares two slurries with different particle sizes, and then mixes the two slurries evenly, so that particles of different particle sizes and mass ratios exist in the mixed slurry at the same time, which facilitates the hydroxy iron phosphate to be more easily in full contact with the lithium source / carbon source, so that lithium ions are more easily embedded in the hydroxy iron phosphate, and then by adding carbon and sintering, a high-density lithium iron phosphate material with a moderate ratio of large and small particles, uniform dispersion, uniform carbon coating and high conductivity is finally obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A flow chart of a method for preparing high-density lithium iron phosphate material from ferric hydroxyphosphate provided in an embodiment of the present invention;
[0018] Figure 2 This is a SEM spectrum of the high-density lithium iron phosphate material prepared in Example 1 of the present invention;
[0019] Figure 3 is the XRD spectrum of the high-density lithium iron phosphate material prepared in Example 1 of the present invention;
[0020] Figure 4 The charge and discharge curves (0.1C and 1C) of the button-type half-cell assembled with the high-density lithium iron phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0022] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides examples of various specific processes and materials, but those of ordinary skill in the art can appreciate the reusability of other processes and / or the use of other materials.
[0023] The embodiment of the present invention provides a method for preparing a high-density lithium iron phosphate material with hydroxy iron phosphate. It should be noted that the high-density lithium iron phosphate material in the present invention refers to a material with a compaction density greater than 2.60 g / cm 3 of lithium iron phosphate material.
[0024] Specifically, if Figure 1 As shown, the method includes:
[0025] Step S1: mixing hydroxyferric phosphate and lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, sand grinding, spray drying, sintering and crushing at a certain temperature to obtain particles A;
[0026] The amount of hydroxyferric phosphate and the lithium phosphate added is according to the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of carbon source added is based on the carbon content in the particle A being between 0.01% and 0.20%; the sand grinding particle size is controlled between 0.50 and 0.90 μm; in spray drying, the inlet air temperature can be 200-220°C, the outlet air temperature can be 80-110°C, the blast frequency can be 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 700-800°C, and the sintering time is 5-15h; the particle size of the particle A is between 3.0 and 10.0 μm.
[0027] In an embodiment of the present invention, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the additive can be one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300-3000ppm.
[0028] Preferably, the hydroxy ferric phosphate is made of ferrous sulfate as a material, and hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate and ammonia water are added to synthesize hydroxy ferric phosphate. Specifically, the hydroxy ferric phosphate can be prepared by the following method: add a phosphorus source and a precipitant to the titanium dioxide byproduct ferrous sulfate, filter press and purify to obtain a ferrous sulfate solution; add an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution; add hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water to the ferrous sulfate solution and react for a period of time to form a mixed slurry, keep the mixed slurry at room temperature for a period of time, and then wash and filter press for many times to form a hydroxy ferric phosphate precursor; flash dry the hydroxy ferric phosphate precursor in a flash evaporator, and sinter at high temperature for a certain period of time to obtain a hydroxy ferric phosphate precursor product; crush the sintered material with a mechanical mill, and mix it with a ribbon mixer to obtain a hydroxy ferric phosphate product.
[0029] Step S2: mixing hydroxyferric phosphate and lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, ball milling, sand milling, spray drying, and then sintering at a certain temperature to obtain particles B;
[0030] The amount of hydroxyferric phosphate and the lithium phosphate added is in accordance with the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; the sand grinding particle size is controlled between 0.40 and 0.80 μm; in spray drying, the air inlet temperature can be 200-220°C, the air outlet temperature can be 80-110°C, the blast frequency can be 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 450-650°C, and the sintering time is 5-15h; the particle size of the particle B is between 2.0 and 5.0 μm.
[0031] In an embodiment of the present invention, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the additive can be one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300-3000ppm.
[0032] Step S3: adding a carbon source, a dopant and a dispersant to the particles A, and then ball milling to obtain slurry C;
[0033] The amount of carbon source added is based on the carbon content in the slurry C being between 1.1% and 1.6%; the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant can be one or more of titanium dioxide and ammonium metavanadate; and the particle size of the slurry C after ball milling is between 0.80 and 1.50 μm.
[0034] Step S4: adding a carbon source, a dopant and a dispersant to the particles B, and then ball milling and sand milling to obtain a slurry D;
[0035] Among them, the amount of carbon source added is based on the carbon content in the slurry D being between 1.1% and 1.6%; the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant can be one or more of titanium dioxide and ammonium metavanadate; the particle size of the slurry D after sand grinding is between 0.20 and 0.50 μm.
[0036] Step S5: uniformly mixing slurry C and slurry D in a certain ratio to obtain mixed slurry E, and then spray drying, sintering, and crushing to obtain a lithium iron phosphate precursor;
[0037] Among them, the addition amounts of the slurry C and the slurry D are according to the mass ratio, slurry C: slurry D = 3:2. In spray drying, the inlet air temperature can be 200-220°C, the outlet air temperature can be 80-110°C, and the blast frequency can be 80Hz; during the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h; during the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the grading frequency is 80-200Hz. The particle size of the final lithium iron phosphate precursor satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
[0038] Step S6: adding a certain amount of carbon source to the lithium iron phosphate precursor and mixing them evenly, and then sintering and crushing them to obtain a high-density lithium iron phosphate material.
[0039] Among them, the mass of the carbon source added accounts for 0.25wt%-2.0wt% of the mass of the hydroxyferric phosphate precursor; the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; during the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h; during the crushing process, the gas pressure is controlled between 0.2-0.4Mpa, the grading frequency is 80-200Hz, and the particle size of the high-density lithium iron phosphate material finally obtained satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
[0040] The method for preparing a high-density lithium iron phosphate material from hydroxy iron phosphate provided in an embodiment of the present invention is to mix hydroxy iron phosphate, lithium phosphate, a carbon source and an additive twice, and then sinter, crush, ball mill and sand mill at different temperatures to obtain two slurries with different particle sizes, and then spray dry, sinter and crush the two slurries according to a certain proportion to obtain a lithium iron phosphate precursor, and then add carbon to the lithium iron phosphate precursor to prepare a high-density lithium iron phosphate material. The method of the present invention first prepares two slurries with different particle sizes, and then mixes the two slurries evenly, so that particles of different particle sizes and mass ratios exist in the mixed slurry at the same time, which facilitates the hydroxy iron phosphate and the lithium source / carbon source to be more easily fully contacted, so that lithium ions are more easily embedded in the hydroxy iron phosphate, and then the high-density lithium iron phosphate material with moderate particle size ratio, uniform dispersion, uniform carbon coating and high conductivity is finally obtained by adding carbon and burning. In addition, the method has low equipment requirements, a simple process flow, and improves production efficiency, and is suitable for application in large-scale industrial production.
[0041] The preparation method provided by the present invention prepares large and small particles through a two-step method, avoiding the limitations of particle grading and the problem of poor consistency in the traditional process route. Ultra-small particles are prepared by a low-temperature solid-phase method, combined with secondary grinding and sintering, and the size and proportion of small particles are controllable and have good dispersibility, achieving a perfect match with other particles. Among them, the first sintering adopts a low-temperature and short-time process to prepare ultra-small particles and reduce manufacturing costs; the secondary sintering adopts high-temperature treatment, which can not only improve the integrity of the coating, but also repair the crystals, and generate primary particles of different sizes at this stage, thereby improving the compaction density and electrochemical properties of the lithium iron phosphate material.
[0042] The specific process and effect of the method for preparing high-density lithium iron phosphate material using hydroxy ferric phosphate of the present invention are further described in detail below in combination with some specific embodiments, but are not limited to the protection scope of the present invention.
[0043] Example 1
[0044] This embodiment provides a method for preparing a high-density lithium iron phosphate material using hydroxy iron phosphate, comprising the following steps:
[0045] Step S1: mixing hydroxyferric phosphate and lithium phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03, and adding a carbon source mixture consisting of sucrose and polyethylene glycol so that the carbon content of the finished product is 0.05% and titanium dioxide with a doping amount of 1000ppm to form a mixture; sand-grinding the above mixture, controlling the sand-grinding particle size to 0.80μm, to obtain a nano-sized sand-grinding slurry; spray-drying the nano-sized sand-grinding slurry, controlling the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz, to obtain a spray material with a spray particle size of D50=20-40μm; placing the above spray material in a box furnace and sintering it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 780°C, and a sintering time of 10h, and then cooling it naturally to obtain a sintered material, and crushing the sintered material by a mechanical crusher to control the particle A of D50=6-10μm;
[0046] Step S2: Mix hydroxyferric phosphate and lithium phosphate in a molar ratio of Li:Fe:P=1.04:1:1.02, and add a carbon source mixture consisting of sucrose and polyethylene glycol so that the carbon content of the finished product is 0.15% and titanium dioxide with a doping amount of 2500ppm to form a mixture; sand grind the above mixture, control the sand grinding particle size to 0.55μm, and obtain a nano-sized sand grinding slurry; spray dry the nano-sized sand grinding slurry, control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz, to obtain a spray material with a spray particle size D50=20-40μm; place the above spray material in a box furnace and sinter it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 500°C, and a sintering time of 8h, and then cool it naturally to obtain particles B;
[0047] Step S3: Particle A and a carbon source consisting of sucrose and polyethylene glycol whose carbon content in the finished product is 1.2% are mixed to form a mixture; the mixture is ball-milled to control the particle size after ball-milling to be 1.2 μm to obtain slurry C;
[0048] Step S4: Particle B and a carbon source consisting of sucrose and polyethylene glycol whose carbon content in the finished product is 1.2% are mixed to form a mixture; the mixture is ball-milled and sand-milled to control the particle size after sand-milling to be 0.20 μm to obtain slurry D;
[0049] Step S5: Mix slurry C and slurry D in a mass ratio of 3:2 for 2h to obtain a mixed slurry E; spray dry the mixed slurry E, control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blowing frequency to 80Hz to obtain a spray material with a spray particle size of D50=20-40μm; place the above-mentioned spray material in a box furnace and sinter it in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 770°C, and a sintering time of 8h, and then cool it naturally to obtain a lithium iron phosphate precursor.
[0050] Step S6: Add 0.50wt% glucose to the lithium iron phosphate precursor, mix for 2h, and then place it in a box furnace for sintering in a nitrogen atmosphere with a heating rate of 3°C / min, a sintering temperature of 770°C, and a sintering time of 6h. After natural cooling and crushing, high-density lithium iron phosphate material can be obtained.
[0051] The SEM spectrum of the lithium iron phosphate positive electrode material prepared according to Example 1 is as follows Figure 2 shown.
[0052] The XRD spectrum of the lithium iron phosphate positive electrode material prepared according to Example 1 is as follows Figure 3 shown.
[0053] Comparative Example 1
[0054] This embodiment provides a method for preparing a high-density lithium iron phosphate material using hydroxy iron phosphate, comprising the following steps:
[0055] Step S1: mixing hydroxyferric phosphate and lithium phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03, and adding a carbon source mixture consisting of sucrose and polyethylene glycol with a carbon content of 1.2% and titanium dioxide with a doping amount of 2500ppm to form a mixture;
[0056] Step S2: sand-grinding the mixture to a sand-grinding particle size of 0.55 μm to obtain a nano-sized sand-grinding slurry; spray-drying the nano-sized sand-grinding slurry to a spraying material with a spray particle size of D50=20-40 μm by controlling the air inlet temperature to 220° C., the air outlet temperature to 100° C., and the air blowing frequency to 80 Hz;
[0057] Step S3: placing the spray material in a box furnace and sintering it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 770°C, and a sintering time of 10 hours, and then cooling it naturally to obtain a sintered material, and crushing the sintered material by a jet mill, controlling the air pressure to 0.35 MPa and the classification frequency to 140 Hz, to obtain a crushed material with a particle size of D10>0.35 μm, D50=0.7-1.8 μm, D90<10 μm, and D100<30 μm;
[0058] Step S4: The above crushed materials are further subjected to screening, batching, packaging and other processes to obtain the finished lithium iron phosphate product.
[0059] In order to verify the quality of the finished lithium iron phosphate material prepared by the method for preparing high-density lithium iron phosphate material by using hydroxy iron phosphate provided in the embodiment of the present invention, the lithium iron phosphate material prepared in the above embodiment 1 and comparative example 1, the conductive agent carbon black and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone according to a mass ratio of 90:5:5, and after being evenly dispersed by ball milling, they are coated on aluminum foil and vacuum dried to obtain a positive electrode. The electrolyte is 1 mol / L LiPF6, wherein the solvent volume ratio is EC:DMC:EMC=1:1:1, the diaphragm is Celgard polypropylene film, and the metal lithium sheet is the negative electrode, which are assembled together into a button half-cell. The test voltage range is 2.0V-3.75V, and the constant current constant voltage charging mode is charged to 3.75V, and the constant current discharge mode is discharged to 2.0V. The charge and discharge current is 0.1C per cycle, and the charge and discharge current is 1C per cycle. The test results are shown in Table 1. Among them, the charge and discharge curves (0.1C and 1C) of the button half-cell assembled with the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention are as follows: Figure 4 shown.
[0060] Table 1. Test items and test results of Example 1 and Comparative Example 1
[0061]
[0062] According to the above examples and control examples and the test results obtained by testing them, the button half-cell prepared by the high-density lithium iron phosphate material prepared in Example 1 has significantly improved 0.1C initial charge and discharge capacity and 1C discharge capacity compared with Comparative Example 1. In addition, the high-density lithium iron phosphate material prepared in Example 1 uses small particles for filling, and the better particle grading ultimately improves the compaction density of the lithium iron phosphate material.
[0063] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0064] Although embodiments of the present invention have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate, characterized in that: The method comprises: Step S1: mixing hydroxyferric phosphate and lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, sand grinding, spray drying, sintering and crushing at a certain temperature to obtain particles A; Step S2: mixing hydroxyferric phosphate and lithium phosphate in a certain ratio, adding a certain amount of carbon source and additives, ball milling, sand milling, spray drying, and then sintering at a certain temperature to obtain particles B; Step S3: adding a carbon source, a dopant and a dispersant to the particles A, and then ball milling to obtain slurry C; Step S4: adding a carbon source, a dopant and a dispersant to the particles B, and then ball milling and sand milling to obtain slurry D; Step S5: uniformly mixing slurry C and slurry D in a certain ratio to obtain mixed slurry E, and then spray drying, sintering, and crushing to obtain a lithium iron phosphate precursor; Step S6: adding a certain amount of carbon source to the lithium iron phosphate precursor and mixing them evenly, and then sintering and crushing them to obtain a high-density lithium iron phosphate material.
2. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In the step S1, the amount of the hydroxyferric phosphate and the lithium phosphate added is based on the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of the carbon source added is based on the carbon content in the particles A being between 0.01% and 0.20%; and the sanding particle size is controlled between 0.50 and 0.90 μm.
3. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In the step S1, during spray drying, the air inlet temperature is 200-220°C, the air outlet temperature is 80-110°C, the blowing frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 700-800°C, and the sintering time is 5-15h; the particle size of the particles A is between 3.0-10.0μm.
4. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the additive is one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300-3000 ppm.
5. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In the step S2, the amount of the hydroxyferric phosphate and the lithium phosphate added is based on the molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the amount of the carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; and the sanding particle size is controlled between 0.40 and 0.80 μm.
6. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In step S2, during spray drying, the air inlet temperature is 200-220°C, the air outlet temperature is 80-110°C, the blowing frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 450-650°C, and the sintering time is 5-15h; the particle size of the particles B is between 2.0-5.0μm.
7. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In step S3, the amount of carbon source added is based on the carbon content in the slurry C being between 1.1% and 1.6%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant is one or more of titanium dioxide and ammonium metavanadate; and the particle size of the slurry C after ball milling is between 0.80 and 1.50 μm.
8. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In step S4, the amount of carbon source added is based on the carbon content in the slurry D being between 1.1% and 1.6%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the dopant is one or more of titanium dioxide and ammonium metavanadate; and the particle size of the slurry D after sand grinding is between 0.20 and 0.50 μm.
9. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In the step S5, the slurry C and the slurry D are added in a mass ratio of slurry C: slurry D = 3:
2. In spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, and the blast frequency is 80Hz; during the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h; during the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the grading frequency is 80-200Hz. The particle size of the lithium iron phosphate precursor finally obtained satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
10. The method for preparing high-density lithium iron phosphate material from hydroxyferric phosphate according to claim 1, characterized in that: In the step S6, the mass of the carbon source added accounts for 0.25wt%-2.0wt% of the mass of the hydroxyferric phosphate precursor; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; during the sintering process, the sintering atmosphere is nitrogen, the sintering temperature is 700-850°C, the heating rate is 3°C / min, and the sintering time is 5-15h; during the crushing process, the gas pressure is controlled between 0.2-0.4Mpa, and the grading frequency is 80-200Hz. The particle size of the high-density lithium iron phosphate material finally obtained satisfies: D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.
Citation Information
Patent Citations
Production method of high-capacity, high-pressure lithium iron phosphate cathode material
CN103618083B
Preparation method of high compaction lithium ion battery positive pole material lithium iron phosphate
CN106744780A
High-compaction lithium iron phosphate material and preparation method thereof
CN111217347A
Preparation method of in-situ graphene-doped low-temperature lithium iron phosphate positive electrode material
CN114229818A
Preparation method of multi-carbon-coated high-compaction lithium manganese iron phosphate
CN115231543A
Cited By
Preparation method of lithium iron phosphate material with high compaction density
CN120039851A
Lithium iron phosphate material, preparation method thereof and lithium ion battery
CN120841482A
Method for preparing ultrahigh-pressure solid lithium iron phosphate from hydroxyl iron phosphate and application of ultrahigh-pressure solid lithium iron phosphate
CN121872345A
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN122025513A